2007
DOI: 10.1186/1471-2318-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort and agitation in older adults with dementia

Abstract: BackgroundA majority of patients with dementia present behavioral and psychological symptoms, such as agitation, which may increase their suffering, be difficult to manage by caregivers, and precipitate institutionalization. Although internal factors, such as discomfort, may be associated with agitation in patients with dementia, little research has examined this question. The goal of this study is to document the relationship between discomfort and agitation (including agitation subtypes) in older adults suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
3
28
1
4
Order By: Relevance
“…Gang et al [10] did not find the effect of cognitive function on physical agitation, but found that the duration of dementia, visual acuity, sleep quality, and physiological discomfort influenced physical agitation. On the other hand, with respect to verbal agitation, previous studies have identified severe pain [13], discomfort [16], and hallucination [35] as the influential factors, suggesting that verbal agitation is affected by sensory perceptual factors. The present study finding that hallucination, physiological discomfort, and pain affected verbal agitation is in line with these previous findings, in that they are health issues related to sensory perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gang et al [10] did not find the effect of cognitive function on physical agitation, but found that the duration of dementia, visual acuity, sleep quality, and physiological discomfort influenced physical agitation. On the other hand, with respect to verbal agitation, previous studies have identified severe pain [13], discomfort [16], and hallucination [35] as the influential factors, suggesting that verbal agitation is affected by sensory perceptual factors. The present study finding that hallucination, physiological discomfort, and pain affected verbal agitation is in line with these previous findings, in that they are health issues related to sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Pelletier and Landreville too [16], discomfort was found to affect verbal agitation. It is difficult for dementia patients to actively communicate physiological discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maioria dos pacientes com demência moderada ou avançada apresenta sintomas psicológicos e comportamentais que, além de aumentar o sofrimento, podem dificultar a assistência do cuidador e precipitar a institucionalização, sobretudo na presença de agitação 32 .…”
Section: Retrogênese Emocionalunclassified
“…Apesar de estudo com autópsia não associar a hiperintensidade da substância branca com envelhecimento patológico 47 , estudos com neuroimagem corroboram a maior prevalência de depressão tardia, comprometimento cognitivo leve, DA, infartos lacunares e menores velocidade psicomotora e flexibilidade cognitiva 21,46,[48][49][50] . A presença de hiperintensidade da substância branca é inversamente proporcional à perfusão cerebral e localiza-se principalmente nas regiões periventriculares e no corpo caloso 32 , sendo o volume dessas alterações estruturais proporcional ao comprometimento cognitivo 48,51 . A alteração da substância branca tem evolução longitudinal e associase aos fatores de risco vasculares do paciente 34 , não sendo modificada ou revertida com o uso de vasodilatadores 45 .…”
Section: Retrogênese Neuropatológicaunclassified